COVID-19 COUNSELING AND TRAINING ON PRODUCE PERSONAL HAND SANITIZER SPRAY AT KWADUNGAN GUNUNG VILLAGE, TEMANGGUNG - Didiek Hardiyanto Soegiantoro; Holy Rhema Soegiantoro; Gregory Hope Soegiantoro (LP2M STP Mataram, 2022)
One of protocol to prevent the spread of covid-19 is to wash your hands with soap and running water or using hand sanitizer. The availability of hand sanitizers in rural areas is still very limited, especially for people who are not used to using hand sanitizers and do not know their functions and uses. In this activity, training and education was carried out to rural communities about the functions, uses, and making of hand sanitizers spray. The method used is counseling and training to 17 peoples from the leaders of Kwadungan Gunung Village, Temanggung. Evaluating the results of participant understanding is done by conducting a pre-test and post-test. From the results of the tests, it was found that there was an increase in the average score of the participants, which means that this education was successful in increasing the participants' knowledge.